2011
DOI: 10.1186/1471-2458-11-450
|View full text |Cite
|
Sign up to set email alerts
|

External review and validation of the Swedish national inpatient register

Abstract: BackgroundThe Swedish National Inpatient Register (IPR), also called the Hospital Discharge Register, is a principal source of data for numerous research projects. The IPR is part of the National Patient Register. The Swedish IPR was launched in 1964 (psychiatric diagnoses from 1973) but complete coverage did not begin until 1987. Currently, more than 99% of all somatic (including surgery) and psychiatric hospital discharges are registered in the IPR. A previous validation of the IPR by the National Board of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
4,435
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 4,126 publications
(4,470 citation statements)
references
References 58 publications
31
4,435
3
1
Order By: Relevance
“…The NPR has a near 100 per cent coverage and yields highly valid data, allowing high‐quality longitudinal epidemiological studies on a population basis19. Reliable, detailed population data from Statistics Sweden for standardization and adjustments further reduced potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…The NPR has a near 100 per cent coverage and yields highly valid data, allowing high‐quality longitudinal epidemiological studies on a population basis19. Reliable, detailed population data from Statistics Sweden for standardization and adjustments further reduced potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…The Swedish national inpatient register (IPR) was established in 1965 and has had complete national coverage since 1987 13. More than 99% of all somatic and psychiatric hospital discharges from across Sweden are registered in the inpatient register.…”
Section: Methodsmentioning
confidence: 99%
“…The data collected by the NHDR are mandatory for all hospitals to provide—including private, public, and other institutions—for both inpatient and outpatient settings. Although coverage and accuracy of both NHDRs is good (Ludvigsson et al 2011, Sund 2012, Huttunen et al 2014), an internal validity control of the data revealed that 2 hospitals in Stockholm, Sweden had performed approximately 1,800 knee arthroscopies annually for degenerative knee disease or meniscal tears in recent years, whereas the number had doubled in 2012, raising suspicion of double-coding of procedures (Socialstyrelsen 2009, Socialstyrelsen 2014). Thus, due to the potential problems with internal validity, we excluded these 2 hospitals in Stockholm from the analysis with regard to the whole study period (2001—2012).…”
Section: Methodsmentioning
confidence: 99%